Shi Wei Ru Xiang pill alleviates acute gouty arthritis through suppressing NLRP3 inflammasome activation - Wang, Na; Zhao, Puchen; Yin, Qin; Li, Lizi; Xu, Haiqi; Yang, Can; Tu, Yanbei; Li, Yanfang (Frontiers in Pharmacology, 2025)
IntroductionShi Wei Ru Xiang pill (SWR) is commonly utilized in Tibetan medicine as a therapeutic intervention for “Huang-shui disease” and has been clinically validated as an effective treatment for acute gouty arthritis (AGA). Nevertheless, the underlying mechanisms of action and the active components of SWR in combating AGA remain unclear.MethodsIn this study, the effects of SWR and its active components on AGA and NLRP3 inflammasome activation were investigated in monosodium urate (MSU)-induced AGA rats and lipopolysaccharide/nigericin-induced THP-1 cells. The chemical profile of SWR was characterized using UPLC-Q-Exactive Orbitrap MS.ResultsThe results indicated that SWR effectively suppressed pyroptosis, caspase-1 activity, and IL-1β production in THP-1 cells. Furthermore, SWR significantly suppressed NLRP3 inflammasome activation and attenuated ankle swelling in a rat AGA model. Specifically, SWR affected the priming and assembly phases to inhibit NLRP3 inflammasome activation. Surprisingly, SWR showed good liver and renal protective effects in AGA rats. A total of 58 compounds were identified in SWR by UPLC-MS analysis. Further pharmacological studies demonstrated that the phenolic compounds serve as active compounds responsible for the inhibition of inflammasome activation, including dehydrocostus lactone, gallic acid, 4-hydroxybenzoic acid.DiscussionThis is the first study to comprehensively elucidate the therapeutic effects and underlying mechanisms of SWR against AGA by inhibiting NLRP3 inflammasome activation. This study strongly indicated that SWR could serve as a promising anti-inflammatory medicine with an acceptable safety profile for the treatment of AGA and other inflammatory disorders linked to NLRP3 inflammasome activation.